Do Attractions ‘Attract’ Tourists? A Comparative Study Four Destinations Using Travel Career Pattern (TCP) and Tourism Product Taxonomy: - Putra, Fajar Kusnadi Kusumah; Ucu Rakhman, Cecep (Centre For Tourism Planning and Development, 2024)
This study aims to explore attractions in four destinations: Australia, Hong Kong, Singapore, and the United Kingdom. The paper sought to answer the following research questions about whether attractions play a different role in attracting travellers or merely satisfying needs. A qualitative research methodology was used to compare different perspectives from four market sources from each destination using the Travel Career Pattern (TCP) theory and tourism product taxonomy. The approach taken in this study is as follows: an exploratory investigation of the existing framework using secondary data from four tourism destinations and market source reports, global tourism statistical reporting data, national tourism organization statistics, consumer trends, travel behaviour, inbound activities, and marketing strategies. The current study found that four existing destinations have their own attractiveness and excellence in pleasure products, human effort, personal search, nature, and business. These results are consistent with previous observational studies in which the role of specific attractions as goal awareness (markers) and motivation (core) is crucial. Each target has its own uniqueness and different roles for different market sources. The generalizability of these results is subject to certain limitations. For example, four destinations and four market sources limit these results. It is recommended that further research be conducted in the following areas to explore more destinations and market sources or, in another case, with the primary data collection for the travellers visiting the destination.